2020
DOI: 10.1186/s13690-020-00444-9
|View full text |Cite
|
Sign up to set email alerts
|

An interpersonal nutrition campaign and maternal knowledge and childhood feeding practices: a case study from mothers in rural Indonesia

Abstract: Background: The purpose of this study was to examine the extent to which a national nutrition communication campaign (NNCC) intervention providing interpersonal communication (IPC) was associated with improved knowledge and behaviors related to feeding practices among mothers with children under two years of age in rural Indonesia. Methods: Data came from a follow-up, cross-sectional survey of 1734 mothers. Key outcomes of interest were minimum meal frequency, minimum dietary diversity and minimum acceptable d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…The health approach, especially nutrition improvement, adopted by the GoBLM in preventing stunting is in line with previous studies that emphasize factors at the individual level as contributors of stunting, for example nutritional intake for pregnant women, nursing mothers and toddlers [4], maternal knowledge [5], and nutritional knowledge [7]. However, stunting also involves factors at the household level (for example, the level of family welfare, household poverty [8][9][10], level of parent education [10], level of family income [16], and family food security [17]) and the environmental level (for example, sanitation and drinking water facilities [22,23]) which have not received serious attention from the GoBLM.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The health approach, especially nutrition improvement, adopted by the GoBLM in preventing stunting is in line with previous studies that emphasize factors at the individual level as contributors of stunting, for example nutritional intake for pregnant women, nursing mothers and toddlers [4], maternal knowledge [5], and nutritional knowledge [7]. However, stunting also involves factors at the household level (for example, the level of family welfare, household poverty [8][9][10], level of parent education [10], level of family income [16], and family food security [17]) and the environmental level (for example, sanitation and drinking water facilities [22,23]) which have not received serious attention from the GoBLM.…”
Section: Discussionsupporting
confidence: 78%
“…Previous research has identified the factors associated with stunting. At the individual level, stunting is associated with low nutritional intake for pregnant women, nursing mothers and toddlers [4], maternal knowledge [5], marriage under 18 years old [6], nutritional knowledge [7]. Certain diseases, for example diarrheal diseases and acute respiratory infection (ARI) [6], can also increase the incidence of stunting.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement observed in mothers' knowledge and practices related to nesia among mothers where they reported an increase of the mothers' level of childhood feeding knowledge [18].…”
Section: Discussionmentioning
confidence: 85%
“…However, it has been voiced by several researchers [3,4]. The results of the literature review show that previous research on stunting is more concerned with: (a) risk factors, for example, the Human Development Index [5], household welfare [6], sanitary facilities and water treatment [7], and service institutions [8], income and employment [9], infectious diseases [10], food insecurity [11], lower birth weight, six months breastfed or more, having parents who were underweight, and mothers who never attended formal education [12]; (b) protective factors, such as direct cash assistance and prosperous rice program (RASTA or Beras Sejahtera), the Program of Family Hope (PKH or Program Keluarga Harapan) [13][14][15], education, maternal knowledge and feeding practices [16][17][18], access to animal products [19]. However, there are not many studies that measure how collaborative practices in governing stunting in Indonesia.…”
Section: Scientifically the Issue Of Governance In Reducing Stuntingmentioning
confidence: 99%